Pengaruh Ukuran Perusahaan, Leverage, dan Profitabilitas terhadap Manajemen Laba - Joe, Sherly; Ginting, Suriani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine and analyze the effect of Firm Size, Leverage, and Profitability on Earnings Management in Manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The population in this study amounted to 208 companies. The sampling method used in this study was purposive sampling method and obtained a sample of 63 companies that became the object of the study with a total of 252 observations. . The research data was obtained from the financial statements of Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2017-2020. The analytical method used is Multiple Linear Regression Analysis. The results showed that simultaneously the variables of Firm Size, Leverage, Profitability had a significant effect on Earnings Management. Partially Company Size has a significant effect on Earnings Management but Leverage and Profitability have no significant effect on Earnings Management in Manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period.